Discovering The Convergence Between Religions and Cultures: An Effective Tool for the Peaceful Co-existence in Pakistan - Dr. Mufti Muhammad Anas Rizwan, (Al Manhal Research Journal, 2022)
Religion, most of the time implicitly, creates culture because religion is also lived as a culture. Religion will always have a cultural "spinoff," because no community can exist exclusively on the basis of clear beliefs. Only when the dominant religion evolves as a culture—that is, as a symbolic, imaginary system that legitimizes the social and political order without making faith a requirement of communal life —can governance function. The distinction between a community and a society is that the foundation of a society is conformity rather than faith. A religious "culture" unwilling to join a more advanced civilization is sometimes perceived as the divide between secularists and believers. Primitive people are consummate believers; civilized people, on the other hand, maintain a residue of belief, but they are also skeptical—and the more skeptical, the more civilized. Culture is frequently associated with religion, and civilization with more general civic phenomena grouped under the title of "civilization." Civilization is frequently thought to be "better" than culture and religion since it is more widespread. While much of the study focuses on religion's negative aspects, it's also crucial to recognize religion's potential for peace building through interfaith dialogue and other religiously driven activities. It was discovered that countries with a higher religious membership tended to be slightly more peaceful. Religion as well as cultures can serve as a motivators or catalysts for achieving peaceful co-existence by resolving conflicts and fostering strong social solidarity. Nevertheless, they can also operate as a type of social cohesiveness, and greater involvement in society, like membership in other groups, can improve the links between citizens, so strengthening the bonds of peace. Pakistan is a country with diverse culture as well as rich historical civilization and majority Muslim population that makes it a perfect place for all the communities to interact and gain a lot of positive aspects from each other’s culture and religion. This will definitely instill tolerance in us which now a days is very much lacking in our society and root cause of many unrests. Also, such inter-communal interactions will drive us towards harmony peaceful co-existence and acceptance of each other’s beliefs and cultural traditions. How religion, culture and civilization are inter-connected and how do these three important factors of society intersect with each other? What impact will this relation and intersection be on peace-building process? How can Pakistan’s rich cultural diversity provide a way forward to potential peaceful co-existence among different communities? This research paper will investigate the gaps that are a breakdown in the peace-building process. Also, it will shed light on a potential roadmap that can be followed using religion, culture and civilization to encourage peaceful co-existence between different communities with special reference to Pakistani society.